HAKIKAT PESERTA DIDIK DALAM PENDIDIKAN ISLAM - Elvy Nur Khoviva; Mohammad Fikri Ramadhani Fauzi; Mukhlisin (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2023)
In the perspective of Islamic educational philosophy, all creatures arebasically learners. God is essentially the educator of all creatures andincluding their education, in the perspective of Islamic educationalphilosophy students include all of God's creatures. Because in essence allhumans are creatures that are always in the process of developing towardsperfection, or the level that is considered perfect, and that process lasts alifetime. In the educational process, students are both subjects and objects ofeducation. They are said to be subjects because they act as the main actors inthe learning process, while they are said to be objects because they are thetargets of students developed by educators. In order for the implementationof the Islamic education process to achieve the desired goals, each learnermust always be aware of his duties and obligations, practice them as the learner's role is. In addition, students are also tasked with maintaining goodrelations with teachers and with fellow friends and to always improve theeffectiveness of learning for themselves.